Immunoreactive beta-melanocyte-stimulating hormone in cerebrospinal fluid and plasma in hypopituitarism: evidence for an extrapituitary origin. Issue 6072 (21st May 1977) - Shuster, S; Smith, A; Plummer, N; Thody, A; Clark, F
Abstract : Immunoreactive beta-melanocyte-stimulating hormone (beta-MSH) was measured in the plasma of 19 patients with hypopituitarism and in the cerebrospinal fluid (CSF) of five of these patients. In neither plasma nor CSF were the beta-MSH concentrations significantly different from those in normal controls. These observations raise the possibility that beta-MSH may be produced by and secreted from neural tissue; this is supported by the findings of beta-MSH in high concentrations in many parts of the brain.